The relationship between Centaurs and Jupiter Family Comets with implications for K–Pg-type impacts. Issue 3 (12th October 2019) - Grazier, K R; Horner, J; Castillo-Rogez, J C
ABSTRACT: Centaurs – icy bodies orbiting beyond Jupiter and interior to Neptune – are believed to be dynamically related to Jupiter Family Comets (JFCs), which have aphelia near Jupiter's orbit and perihelia in the inner Solar system. Previous dynamical simulations have recreated the Centaur/JFC conversion, but the mechanism behind that process remains poorly described. We have performed a numerical simulation of Centaur analogues that recreates this process, generating a data set detailing over 2.6 million close planet/planetesimal interactions. We explore scenarios stored within that data base and, from those, describe the mechanism by which Centaur objects are converted into JFCs. Because many JFCs have perihelia in the terrestrial planet region, and since Centaurs are constantly resupplied from the Scattered Disc, the JFCs are an ever-present impact threat.